Aging-Shifted Prostaglandin Profile in Endothelium as a Factor in Cardiovascular Disorders - Hao Qian; Na Luo; Yuling Chi (Journal of Aging Research)
Age-associated endothelium dysfunction is a major risk factor for the development of cardiovascular diseases. Endothelium-synthesized prostaglandins and thromboxane are local hormones, which mediate vasodilation and vasoconstriction and critically maintain vascular homeostasis. Accumulating evidence indicates that the age-related changes in endothelial eicosanoids contribute to decline in endothelium function and are associated with pathological dysfunction. In this review we summarize currently available information on aging-shifted prostaglandin profiles in endothelium and how these shifts are associated with cardiovascular disorders, providing one molecular mechanism of age-associated endothelium dysfunction and cardiovascular diseases.